Effect of dents in laminated carbon composite beams on modified anisotropic electric potential analysis. (15th September 2018) - Todoroki, Akira; Yamane, Takuya
Abstract: Because carbon fiber reinforced polymer (CFRP) laminated composites have electric conductivity, damage monitoring was performed using electrical resistance changes. The authors previously proposed an anisotropic electric-potential function method to calculate the electric-potential field of laminated CFRP composites. The method, however, did not deal with the effects of dents. The present study deals with the effects of dents on the anisotropic electric-potential function method. The dent causes an electric conductivity increase in the through-thickness direction. The increase was modeled and applied to a beam-type specimen. The results were compared with the finite-element method results, and the method using equivalent conductivity in the through-thickness direction was confirmed to be effective.